Vaccination Management in the Republic of Poland and in Selected Countries - Krukowska-Miler, Agata (Journal of Public Governance, 2023)
Objectives: The aim is to look at the vaccination management process, which may lead to its improvement. The article focuses on the analysis of management activities in healthcare, the vaccination process, and its impacton the development of the pandemic. It will show not only information about the pandemic, but, most of all, the impact of actions on the spread of the disease compared to other countries at different times.Research Design & Methods: The main research method includes a critical analysis of secondary data. The study covers the period from January to April, 2021.Findings: Operating in a situation where raw materials (vaccines) are of a limited availability and the social and economic situation is difficult (pandemic) poses challenges. This situation is completely new to the wholeworld and as such requires a new perspective on the problem. The thesis that good management contributes to the improvement of a given process is confirmed.Implications/Recommendations: Secondary research, illustrating the course of the vaccination process in various countries, has shown that it is possible to create an optimal vaccine management method only by taking intoaccount the elements that make up the socio-cultural and political factors.Contribution/Value Added: The hypothesis in this article was based on the statement that there is an optimal crisis management based on the experiences of different countries and the meeting of their different methods of organising vaccination against SARS-CoV-2. From the point of view of economic sciences, it is a novel topic, because, for the first time. it is possible to examine the relationship between health policy and the state of a global epidemic in the era of general access to information, fast data transfer, high mobility, and globalisation.Article Classification: review articleJEL classification: I110